Morbidity pattern and psychosocial problems of elderly in a rural population of Uttar Pradesh, India: a cross-sectional study - Seth, Rajesh Kumar (International Journal of Research in Medical Sciences, 2016)
Background: Ageing is a universal process and it affects every individual, family, community and society. It is a normal, progressive and irreversible process. Ageing is generally defined as a process of deterioration in the functional capacity of an individual that results from structural changes, with advancement of age. Population ageing is a global phenomenon. Aim of the study was to study the morbidity profile and their psychosocial problems of the elderly in a rural population in the state of Uttar Pradesh, India. Methods: This was a cross-sectional community based descriptive study. People of either sex, more than 60 yrs of age residing in the field practice areas of department of community medicine constituted the study population. Socio-demographic information like name, age, sex, religion, education, occupation etc. and other information like housing, ventilation, overcrowding were collected in semi-structured and pretested proforma, after obtaining informed consent. The multi-stage sampling methodology was adopted for the selection of study unit. Results: A total of 272 elderly with 173 male and 99 females were interviewed in this study. About one fourth of the elderly belonged to age 60-61 years (25.7%). More than half of the elderly had a fall within last 12 months (66.2%). Not much difference was observed in the percentage of fall within 12 months in male (64.7%) and females (68.7%). The majority of the males (64.7%) and females (81.8%) had pain in joints as the presenting symptom. The second most common symptom was found to be weakness. Only 45.6% of the elderly were satisfied with their life. There was similar percentage of male (45.7%) and female (45.5%) elderly who were satisfied with their life. However, 51.8% felt empty in their life and 45.2% preferred to stay in the house. Conclusions: The need for the hour is to set up special health services for geriatric population in accordance with the common existing problems. Providing screening services as well as curative, rehabilitative services and convalescent homes to provide long term care is also a priority.